Radiation Therapy for Chemotherapy Refractory Gingival Myeloid Sarcoma - Lee, Daniel Y.; Baron, Jonathan; Wright, Christopher M.; Plastaras, John P.; Perl, Alexander E.; Paydar, Ima (Frontiers in Oncology, 2021)
Gingival myeloid sarcoma (MS) refractory to induction chemotherapy is a rare clinical entity and can be treated with palliative radiation therapy (RT). However, there are few previously published reports of RT approaches for the treatment of gingival MS. We present a single institution retrospective observational study of adult patients treated with palliative RT for chemotherapy refractory gingival MS. A total of 6 patients diagnosed with gingival MS in the setting of relapsed or refractory acute myeloid leukemia treated with palliative RT were identified, with a median age of 66 (range 52-77). Patients were treated with radiation doses ranging from 5-20 Gy in 2-10 fractions. Two patients had adequate follow up time to assess treatment response. One patient who was simulated with PET/CT experienced a local complete response, while the other patient required retreatment 2 months after initial treatment and experienced an eventual local partial response. Three patients experienced radiation mucositis, with one patient experiencing grade 5 toxicity attributed to concomitant treatment with the radiosensitizer hydroxyurea. We believe that this study can provide a practical reference point for other clinicians given the rarity of gingival MS requiring palliative radiation therapy as a clinical entity.